Identifying the richness and evolutionary relationships of Ranunculus sect. Batrachium in its diversity centre in south-western Europe - Prančl, Jan; Koutecký, Petr; Lučanová, Magdalena; Nagy Nejedlá, Michaela; Brožová, Viktorie; Dolejšek, Vojtěch; Košnar, Jiří; Trávníček, Pavel; Kaplan, Zdeněk (Scientific reports, 2025)
Aquatic plants are generally attributed to have larger ranges than their terrestrial counterparts, but this knowledge is often hindered by insufficient exploration of their diversity. To fill this gap, we investigated the taxonomically extremely challenging aquatic plant group Ranunculus sect. Batrachium in south-western Europe, which is an important glacial refugium, using flow cytometry, chromosome counting and DNA sequencing (ITS nuclear region and two non-coding plastid regions). In a dataset comprising 587 individuals from 117 localities, we detected 36 cytotypes across seven ploidy levels, which included a considerable proportion of previously unrecognized diversity consisting of three high ploidies (7x, 10x, 12x), seven cryptic species, two additional unclassifiable biotypes and nine hybrids. Two thirds of the taxa are polyploid, with many species presumed to be of allopolyploid origin. We discovered a remarkably close relationship between the local cytotype of R. peltatus s.l. and the morphologically distinct, widespread and ecologically specialized species R. fluitans; the latter might have evolved as a result of rapid adaptation to newly colonized river habitats in the early postglacial period. Undeniably, diversity within this group is still incompletely understood and is far more complex than current taxonomic concepts suggest.
Keywords: Biodiversity; Hybridization; Ranunculus; Chromosome number; genetická variace; fylogeneze; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; biodiverzita; Europe; molekulární evoluce; ploidie; biologická evoluce; Evolution, Molecular; Cryptic variation; DNA rostlinná; Evropa; DNA, Plant; Biological Evolution; Genome size; Molecular identification; Polyploidy; Genetic Variation; Ploidies; polyploidie